Trigger Happy Grime Stoppers - Slatter, Bruce (Edith Cowan University, 2014)
How we understanding of the complexity of human aggression through the objects we encounter is a question posed in this research. The series Trigger Happy; Grime Stoppers uses confiscated and redundant rifle butts. The work belongs to a field of enquiry that is referred to as object sculpture and continues questions raised by the ready-made artists and assemblage sculptors. These six carved sculptures extend research into the redeployment and reconfiguration of objects through sculptural process. The partial transformation of six wooden gun butts into domestic cleaning bottles draw parallels between the measure and use of force and aggression in two quite differing spaces, that of the domestic space and the criminal underworld.